Interruption of β-Catenin Signaling Reduces Neurogenesis in Alzheimer's Disease - He, Ping; Shen, Yong (The Journal of neuroscience, 2009)
The neuronal loss associated with Alzheimer's disease (AD) affects areas of the brain that are vital to cognition. Although recent studies have shown that new neurons can be generated from progenitor cells in the neocortices of healthy adults, the neurogenic potential of the stem/progenitor cells of AD patients is not known. To answer this question, we compared the properties of glial progenitor cells (GPCs) from the cortices of healthy control (HC) and AD subjects. The GPCs from AD brain samples displayed reduced renewal capability and reduced neurogenesis compared with GPCs from HC brains. To investigate the mechanisms underlying this difference, we compared β-catenin signaling proteins in GPCs from AD versus HC subjects and studied the effect of amyloid β peptide (Aβ, a hallmark of AD pathology) on GPCs. Interestingly, GPCs from AD patients exhibited elevated levels of glycogen synthase kinase 3β (GSK-3β, an enzyme known to phosphorylate β-catenin), accompanied by an increase in phosphorylated β-catenin and a decrease in nonphosphorylated β-catenin compared with HC counterparts. Furthermore. we found that Aβ treatment impaired the ability of GPCs from HC subjects to generate new neurons and caused changes in β-catenin signaling proteins similar to those observed in GPCs from AD patients. Similar results were observed in GPCs isolated from AD transgenic mice. These results suggest that Aβ-induced interruption of β-catenin signaling may contribute to the impairment of neurogenesis in AD progenitor cells.